Control interno contable y su incidencia en los estados financieros de la empresa Netsurtv S.A en el periodo 2022. - Torres Honores, Joselyn Michelle (Machala : Universidad Técnica de Machala, 2023)
This investigation is on the internal accounting control applied within the company netsurtv s.a with regard to the audit area, which allows us through its analysis to identify the factors involved in the improvement of functions both internally and externally. The objective lies in implementing the internal accounting control and its incidence on the financial statements of the company netsurtv s.a in the 2021 period, in order to analyze the deficit that is being taken on the income statement and financial statement, since the procedures of internal controls that have been managed have not been precise to promote business growth and fluidity of the company's liquidity. The methodology that was used within the investigation was the historical-logical and analytical- deductive, likewise the empirical methods used are the survey and study of documents; the development of an internal control will allow obtaining reliable, timely, efficient and effective financial statements, for this it will also be required to apply the accounting policies correctly by the personnel that works in the company.
Esta investigación es sobre el control interno contable que se aplica dentro de la empresa Netsurtv S.A con respecto al área de auditoría, que mediante su análisis nos permite identificar los factores que intervienen en el mejoramiento de las funciones tanto internamente como externamente. El objetivo radica en implementar el control interno contable y su incidencia en los estados financieros de la empresa Netsurtv S.A en el periodo 2021, para con ello analizar el déficit que se está teniendo sobre el estado de resultados y estado financiero, ya que los procedimientos de control interno que se han venido manejando no han sido los precisos para fomentar el crecimiento empresarial y fluidez de la liquidez de la empresa. La metodología que se utilizó dentro de la investigación fue el historico-logico y analítico-deductivo, así mismo los métodos empíricos utilizados son la encuesta y estudio de documentos; el desarrollo de un control interno permitirá obtener estados financieros confiables, oportunos, eficientes y eficaces, para ello también se requerirá aplicar las políticas contables correctamente por parte del personal que labora en la empresa.
Keywords: CONTROL INTERNO CONTABLE; ESTADOS FINANCIEROS; POLITICAS CONTABLES